THE EFFECT OF JIGSAW STRATEGY ON THE ABILITY OF THE FIRST YEAR STUDENTS OF SMK N 2 KEPENUHAN ROKAN HULU IN COMPREHENDING RECOUNT TEXT - Fitri Andriyanti; Jismulatif Jismulatif; Fakhri Ras (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This pre-experimental research was aimed to find out whether or not there was a significant effect of Jigsaw strategy on the ability of the first year students of SMKN 2 Kepenuhan Rokan Hulu in comprehending recount text. This research design used one group pre-test and post-test. The sample of this research are taken by using cluster random sampling technique and that falls to Tata Busana class as big as 25 students. The data were collected by multiple choice tests. The data analyzed by using SPSS 23.00. The result of the data analysis showed that mean score of the pre-test was 59.50 and the mean score of post-test was 74.80. In other words, the mean score of the post-test was higher than the pre-test. The result also showed that the value of t-test was higher than t-table (2.49 > 1.71) at significance level of 5%. It can be concluded that Alternative Hypothesis was accepted. Thus, there was a significant effect of jigsaw strategy on the ability of the first year students of SMKN 2 Kepenuhan Rokan Hulu in comprehending recount text. The implication of the findings was that the students should study in group like Jigsaw and more focus on the given tasks to increase their vocabulary items. Key Words: Jigsaw, Reading Comprehension, Recount Text